MENUJU MODEL EKONOMI REGENERATIF: INTEGRASI KONSEP ISRĀF DALAM TRANSFORMASI SIRKULARITAS EKONOMI KONTEMPORER - Mohammad Romli (JSE: Jurnal Sharia Economica, 2026)
The global ecological crisis stems from the ontological failure of the linear economic system, which separates material activity from spiritual values. This study aims to formulate an integrative framework between the Islamic prohibition of isrāf (excessiveness) and contemporary circular economy transformations to foster a regenerative model. Using a qualitative library research method, this research analyzes authoritative Islamic texts alongside regenerative economic discourses. The results confirm that while the circular economy provides technical mechanisms for resource retention, the concept of isrāf acts as a vital "moral brake" against overconsumption. This synthesis creates "Transcendental Circularity," shifting the paradigm from secular anthropocentrism to a theocentric-khilafah approach. The findings demonstrate that integrating transcendental values corrects the systemic "rebound effect" of modern technology and provides a solid ethical foundation for sustainable production and consumption. This research contributes to the Islamic economic discourse by offering a holistic guide for green policy-making. In conclusion, the synergy between modern science and spiritual ethics is essential to resolve the ontological failures of modern economics and ensure ecological justice for future generations.